Mesoporous TiO2-based architectures as promising sensing materials towards next-generation biosensing applications. Issue 5 (6th January 2021) - Amri, Fauzan; Septiani, Ni Luh Wulan; Rezki, Muhammad; Iqbal, Muhammad; Yamauchi, Yusuke; Golberg, Dmitri; Kaneti, Yusuf Valentino; Yuliarto, Brian
Abstract : This review highlights the recent development of mesoporous TiO2 -based architectures as promising sensing materials for diagnosing diseases and detecting harmful substances in the human body. Abstract : In the past two decades, mesoporous TiO2 has emerged as a promising material for biosensing applications. In particular, mesoporous TiO2 materials with uniform, well-organized pores and high surface areas typically exhibit superior biosensing performance, which includes high sensitivity, broad linear response, low detection limit, good reproducibility, and high specificity. Therefore, the development of biosensors based on mesoporous TiO2 has significantly intensified in recent years. In this review, the expansion and advancement of mesoporous TiO2 -based biosensors for glucose detection, hydrogen peroxide detection, alpha-fetoprotein detection, immobilization of enzymes, proteins, and bacteria, cholesterol detection, pancreatic cancer detection, detection of DNA damage, kanamycin detection, hypoxanthine detection, and dichlorvos detection are summarized. Finally, the future perspective and research outlook on the utilization of mesoporous TiO2 -based biosensors for the practical diagnosis of diseases and detection of hazardous substances are also given.